Long-term lime and gypsum amendment increase nitrogen fixation and decrease nitrification and denitrification gene abundances in the rhizosphere and soil in a tropical no-till intercropping system - Bossolani, João William [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Merloti, Luis Fernando; Moretti, Luiz Gustavo [UNESP]; Costa, Nídia Raquel [UNESP]; Tsai, Siu Mui; Kuramae, Eiko Eurya (Elsevier, 2020)
Liming is widely used to decrease soil acidity, and the application of lime alone or in combination with other amendments, such as gypsum, is a viable agricultural practice to improve soil nutrient status and crop yield. However, the effects of applying lime and gypsum alone or in combination on the microbial population and N cycle in intercropped no-till tropical systems are largely unknown. Here, we determined the lasting effects of applying lime and gypsum individually or in combination on soil chemical properties, N uptake by intercropped plants, maize yield, archaeal and bacterial abundances, and N cycle genes in the maize and ruzigrass rhizospheres in a long-term field experiment in tropical soil with a no-till maize and forage ruzigrass intercropping system. Our results showed that the application of lime or lime + gypsum increased soil fertility and the gene abundances of microorganisms responsible for biological nitrogen fixation and reduced gene abundances of nitrification and denitrification in the soil and rhizosphere of ruzigrass and maize. The accompanying increases in Ca2+ and Mg2+ availability, reduced Al3+ levels, and balance of micronutrient availability, mainly Mn, in the soil strongly influenced the responses of N cycle genes and enhanced plant N-acquisition and maize yield.
Keywords: Crops; N cycle genes; Soil quality; Urochloa ruziziensis; Zea mays